Comparison Study of Electromyography Using Wavelet and Neural Network - Gheab, Nebras Hussain; Saleem, Sadeem Nabeel (Al-Khwarizmi Engineering Journal, 2019)
In this paper we present a method to analyze five types with fifteen wavelet families for eighteen different EMG signals. A comparison study is also given to show performance of various families after modifying the results with back propagation Neural Network. This is actually will help the researchers with the first step of EMG analysis. Huge sets of results (more than 100 sets) are proposed and then classified to be discussed and reach the final.